Fenologia de ubaia-azeda (Eugenia azeda Sobral, Myrtaceae) - Moreira, Víctor de Paiva (2021)
The Myrtaceae family is one of the most diverse in the Neotropics and of great generation for restinga ecosystems, having structural importance, high wealth and abundance and in addition to sustaining the fauna. The species Eugenia azeda Sobral is typical of this environment and important for communities in Rio Grande do Norte and Ceará. Although used by local populations, being found in street markets, this species was only described in 2010. Therefore, there are still gaps in knowledge about its ecology and, considering its high food and economic potential, it is urgent to know more about its reproductive biology. That said, the objective of this work was to describe and quantify the phenological patterns (budding, leaf fall, flower buds, anthesis flowers, immature fruit and ripe fruit) of the E. azeda in a coastal vegetation fragment in Macaíba / RN, and to test whether there is a relationship between its phenophases and meteorological variables (precipitation, photoperiod and maximum, average and minimum temperature). For this, 30 individuals of the species were monitored for 2 years (January 2018 to December 2019), classifying the intensity of phenophases by a semi-quantitative method (Fournier) and their activity index. Spearman's correlation between phenophases and recorded meteorological variables was then evaluated. Based on the data obtained, it was possible to conclude that E. azeda presents a seasonal behavior for budding, flowering and fruiting phenophases. Leaf sprouting occurred during almost the whole year, with the exception of part of the dry season, between October and December. Leaf fall was a continuous event throughout the year, with no seasonality. Flower buds and anthesis flowers were recorded at the end of the dry season (December to January) and at the end of the rainy season (July to September). Immature fruits were found from the end of the rainy season to its beginning, including the dry season (August to March), while the ripe fruits were seen only at the beginning of the rainy season (December to February). Therefore, a positive correlation was obtained between precipitation, sprouting and the production of ripe fruits, and the photoperiod and temperatures with the production of immature and ripe fruits. From these data it was possible to identify which meteorological variables are associated with the behavior of E. azeda. t was possible to define that the best period for collecting the fruits is between February and March. In future works, an evaluation on more sensitive temporal and spatial scales is suggested to better understand the relationship between the environment and its phenological responses.